The Role of Employer Branding in Work-life Balance and Employee Retention Relationship among Generation Z Workers: Mediation or Moderation? - Evelyn Hendriana; Albert Christoper; Handika Oemardi Adhitama Zain; Natasha Pricilia (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to investigate two models that examine the role of employer branding in the relationship between work-life balance and employee retention in Generation Z workers.  Design/Methods/Approach: This study applied quantitative methods by distributing questionnaires using google forms. A purposive sample of 189 Generation Z workers in Greater Jakarta, Indonesia, was used to test the models. The data was processed using SmartPLS 3 Software. Findings: The results of the PLS-SEM analysis revealed a significant relationship between work-life balance, job stress, emotional exhaustion, and employee retention. Instead of mediating the relationship between work-life balance and employee retention, this study revealed that employer branding significantly moderated the relationship between emotional exhaustion and employee retention among Generation Z workers. These findings could be used to develop a human capital strategy to retain Generation Z employees. Originality/Value: Among many studies on the relationship between work-life balance and employee retention, only a few focus on Generation Z workers. This generation also places greater emphasis on employer branding when considering their workplace. However, employer branding is rarely integrated into work-life balance research. This study extends the application of social exchange theory to explain the relationship between work-life balance (WLB) and employee retention by integrating employer branding into the model. Practical/Policy implication: Given the results, organizations may provide flexibility that enables employees to work from anywhere and anytime. Moreover, companies must design strategies to manage WLB, such as flexible working hours to allow employees to manage their work schedules according to their needs and reduce workplace conflicts. Companies are advised not to assign responsibilities that do not correspond to the employee's position or job description. Organizations may provide mindfulness training through meditation during breaks or before and after work hours to help them relax from their workload and avoid emotional exhaustion. Lastly, companies must engage in internal marketing activities by creating positive work culture, designing clear career paths, providing training, offering attractive benefits, and providing opportunities for employees to grow and develop.